Market development and policy for One Belt One Road. (Elsevier, 2022)
The Belt and Road initiative is marketed by the Chinese government as the "twenty-first century maritime Silk Road and the "Silk Road economic belt. The initiative encourages policy coordination, trade facilitation, financial integration, and transport connectivity. The Belt and Road initiative covers at least 65 countries across Asia, Africa, the Middle East, and Europe, involving 70% of the global population, 75% of world energy reserves and 55% of world GNP. Such an initiative is expected to bring significant impacts to the transport and logistics industry in the regions involved. The transport and logistics sector not only directly contributes to the production of transport and logistics services, but also provides essential inputs to other sectors such as tourism, trade, infrastructure investment and management. Therefore, it is important to jointly analyse the implications of the Belt and Road initiative to the transport and logistics sectors, the best strategies and operation practices that the industry can pursue, and the right government policies that should be implemented in relation to the initiative. This volume will be the first in Elsevier's China Transportation Series, from series editor Paul Tae-Woo Lee. If you are interested in writing or editing for the series, please contact Dr. Lee: paultaewoo.lee@zju.edu.cn.